2020
DOI: 10.5194/acp-2020-1189
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhanced secondary organic aerosol formation from the photo-oxidation of mixed anthropogenic volatile organic compounds

Abstract: Abstract. Motor vehicle exhaust is one of the important contribution sources of secondary organic aerosol (SOA) in urban areas. Long-chain alkanes and aromatic hydrocarbons are included in gaseous organic pollutants of vehicle emissions, representative for diesel and gasoline vehicles respectively. In this work, the SOA production from individual anthropogenic volatile organic compounds (AVOCs) (n-dodecane, 1,3,5-trimethylbenzene) and mixed AVOCs (n-dodecane + 1,3,5-trimethylbenzene) were studied with a large-… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 69 publications
(93 reference statements)
0
3
0
Order By: Relevance
“…On the other hand, the effect of VOC mixtures on SOA formation is not conclusive and may enhance or suppress SOA in different studies 23,[30][31][32][33] . For example, Li et al 31 found enhanced SOA formation by mixing two anthropogenic VOCs (n-dodecane and 1,3,5-trimethylbenzene) in the presence of NO x and sunlight, and their experiments were conducted in a large-scale outdoor chamber, which is close to the real atmospheric conditions.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…On the other hand, the effect of VOC mixtures on SOA formation is not conclusive and may enhance or suppress SOA in different studies 23,[30][31][32][33] . For example, Li et al 31 found enhanced SOA formation by mixing two anthropogenic VOCs (n-dodecane and 1,3,5-trimethylbenzene) in the presence of NO x and sunlight, and their experiments were conducted in a large-scale outdoor chamber, which is close to the real atmospheric conditions.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, the effect of VOC mixtures on SOA formation is not conclusive and may enhance or suppress SOA in different studies 23,[30][31][32][33] . For example, Li et al 31 found enhanced SOA formation by mixing two anthropogenic VOCs (n-dodecane and 1,3,5-trimethylbenzene) in the presence of NO x and sunlight, and their experiments were conducted in a large-scale outdoor chamber, which is close to the real atmospheric conditions. By contrast, Voliotis et al 32 found that the volatility of SOA from anthropogenic and biogenic VOC mixtures (o-cresol and α-pinene) was in between those measured in single-VOC systems, and their experimental conditions were representative of typical ambient daytime photochemistry with moderate relative humidity (50 ± 5%) and temperature (24 ± 2 °C).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation